Multi-parameter optimizations of elastic chain catenary based on response surface methodology for high-speed railway - Zhang, Zongfang; Zhang, Maoyou (Frontiers in Mechanical Engineering, 2025)
As train operating speeds increase, the quality of pantograph-catenary current collection deteriorates, sometimes even resulting in contact loss. To ensure stable current collection during high-speed operation, it is crucial to optimize the design parameters of the catenary system. This study employs finite element analysis and constructs a pantograph-catenary coupling model using MSC. Marc software to simulate the coupled motion between the catenary and the pantograph. During the research process, the primary technical challenge was accurately evaluating the comprehensive effects of multi-parameter variations on pantograph-catenary current collection quality. First, we independently analyzed the effects of catenary tension and linear density variations on contact pressure to clarify the mechanisms of individual parameter influences. However, recognizing that multiple parameters might change simultaneously in actual operations, we introduced the Response Surface Methodology (RSM) to deeply explore the combined effects of two parameters on current collection quality. The innovation of this study lies not only in considering the effects of individual parameters but also in systematically analyzing the impact of multi-parameter interactions using RSM. Furthermore, from the perspective of the combined effects of catenary tension and contact wire linear density, we proposed an optimized catenary design scheme for the 500 km/h high-speed train operation scenario. Specifically, by increasing the contact wire tension, reducing the messenger wire tension, and lowering the linear density of the contact wire, we can significantly improve pantograph-catenary current collection quality, thereby providing robust support for the safe and stable operation of high-speed railways. In conclusion, this study addresses key technical challenges in multi-parameter optimization and proposes a practical optimization scheme with significant application value, offering important references for the design and optimization of high-speed railway catenary systems.